2016
DOI: 10.1515/aslh-2016-0013
|View full text |Cite
|
Sign up to set email alerts
|

A Methodology for Experimental Research of the Freezing Process of Logs

Abstract: This paper describes a methodology for experimental research of the change in the temperature and humidity of the air processing medium and also in the temperature at 4 points of the longitudinal section of logs during freezing. The suggested methodology is used to research the change in the mentioned parameters of poplar logs with diameters of 240 mm, lengths of 480 mm and moisture content above the hygroscopic range during 50 h of freezing in a freezer at a temperature of about -30 °C. The automatic measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 8 publications
1
15
0
Order By: Relevance
“…(16) make the mentioned curves more lenient. During our simulations with the model, using the approach suggested above and the mathematical descriptions of Q v-fw and Q v-bw , we obtained good qualitative and quantitative conformity between the calculated and experimentally determined temperature distribution in the log's longitudinal section during the whole process of the freezing of both the free and the bound water not only in the studied beech log for the purposes of this paper, but also many other logs above the hygroscopic range (including the poplar logs presented in Deliiski -Tumbarkova (2016).…”
Section: Figure 5 Change In Q V-fw Q V-bw and Q V-total During Thsupporting
confidence: 67%
See 4 more Smart Citations
“…(16) make the mentioned curves more lenient. During our simulations with the model, using the approach suggested above and the mathematical descriptions of Q v-fw and Q v-bw , we obtained good qualitative and quantitative conformity between the calculated and experimentally determined temperature distribution in the log's longitudinal section during the whole process of the freezing of both the free and the bound water not only in the studied beech log for the purposes of this paper, but also many other logs above the hygroscopic range (including the poplar logs presented in Deliiski -Tumbarkova (2016).…”
Section: Figure 5 Change In Q V-fw Q V-bw and Q V-total During Thsupporting
confidence: 67%
“…Based on the data in the references cited above, the value of 3.34•10 5 J•kg -1 as constant for the specific latent heat for both the free and the bound water in the wood materials has been accepted in the present paper. Our wide experiments with different wood species showed that the free water freezing occurs in the small range from 0 o C to -1 o C (Deliiski -Tumbarkova 2016). This means that the acceptance of the non-temperature dependent constant value of 3.34•10 5 J•kg -1 as a specific latent heat of the free water is correct.…”
Section: Mathematical Description Of the Internal Heat Sources In Logmentioning
confidence: 68%
See 3 more Smart Citations